LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK MODELING UNTUK MENCEGAH PERILAKU BULLYING PESERTA DIDIK DI SMAN 1 SINDANGKERTA - Tima Melati; Teti Sobari; Muhammad Rezza Septian (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
This research was carried out with the aim of knowing the implementation of group guidance services with modeling techniques, student responses, knowing the difficulties experienced by students and knowing the obstacles faced by BK teachers when implementing group guidance services with modeling techniques to prevent bullying behavior in students. class XI. The method used in this research is descriptive qualitative method. The subjects of this study were six class XI participants who were selected based on the results of observations and interviews so that students would not become bullies. The data collection procedure used observation and interviews. Data analysis in this study used source triangulation through the data collection stage, the data reduction stage, the data display stage, and the conclusion drawing stage. Based on the results of providing group guidance services with modeling techniques to prevent bullying behavior in SMAN 1 Sindangkerta students that the implementation of services provided by BK teachers is in accordance with the RPL made and proven to help guidance and counseling teachers in preventing bullying behavior in students, then The response shown by students was very good, it was seen from the enthusiasm of students in participating in this activity, students had obstacles when participating in the service, namely students did not focus on the material provided by the BK teacher, then the obstacle for the BK teacher was in the process of providing services at the activity stage. students tend to be less focused so that guidance and counseling teachers must be more creative in an effort to restore focus on students. Keywords: Group guidance, modeling, bullying